Right-ventricular involvement in acute myocarditis assessed by cardiac magnetic resonance feature tracking. (4th February 2022) - Bonanni, M; Angelini, G; Paiocchi, VL; Leo, LA; Schlossbauer, SA; Pasotti, E; Pedrazzini, G; Valgimigli, M; Sangiorgi, GM; Faletra, FF; Pavon, AG
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: the prevalence of right ventricular (RV) involvement in acute myocarditis (aMY) has been poorly investigated. Actually, RV evaluation may be difficult in echocardiography and scar detection as well as the presence of edema in cardiovascular magnetic resonance (CMR) may be challenging due to small RV wall thickness. We sought to examine the incremental diagnostic value of CMR feature tracking (FT) in RV strain-analysis for patients with aMY. METHODS: all consecutive patients with clinically suspected aMY were enrolled in our study. Inclusion criteria were: 1) new ECG abnormalities 2) myocardial cytolysis markers and 3) absence of angiographically detectable coronary artery disease. Exclusion criteria included poor cine image quality caused by respiratory motion and arrhythmias. All patients underwent transthoracic echocardiography (TTE) and CMR within hospitalization on a 3T scan. CMR protocol included current standard Lake Louise criteria (LLC) for myocarditis and T2 weighted images. The definite diagnosis was made when 2 or more Lake Louise criteria were fulfilled. FT analysis of the left ventricle (LV) and RV was performed using the Tissue Tracking Module to obtain LV and RV global longitudinal (RV-GLS) strain data. 20 sex and aged matched individuals who underwent to CMR for suspected cardiac disease, which was not confirmed thereafter, were considered as control population. RESULTS: 52 patients were included in the study, mean age was 36 ± 17 years, three patients were female (6%). Mean LV ejection fraction (EF) was 56, 2 ± 7, 2 and mean end-diastolic volume indexed (EDVi) was 62, 52 ± 19, 02 ml/mq. 10 patients (19%) had impaired EF with mean values of 44, 6 ± 6, 1%. All patients have normal RV function evaluated in TTE considering tricuspid annular plane systolic excursion (TAPSE) (22, 7 ± 2, 4mm). No kinetic abnormalities were reported. All patients underwent CMR within 3 ± 1 days. Normal RV-EF, normal volumes and no RV kinetic abnormalities were reported in all cases also in CMR examination. aMY was confirmed in all patients with the presence of myocardial oedema and subepicardial late gadolinium enhancement (LGE).  Inferior segments were involved in 28 patients (54%), lateral segments in 19 patients (37%), septal segments in 7 patients (13%) and anterior segments in 15 patients (29%).  RV-GLS was -21, 5 ± 5, 6% which was not significantly different from control population (-23, 01 ± 3, 63; p value= 0, 201). Globally, 34 patients (65%) had an aMY involving inferior and lateral segments. In this subgroup, RV-GLS was significantly lower compared to other aMY (-19, 8 ± 5, 7 vs -23, 9  ± 4, 6 p value = 0, 047) and compared to control population (-19, 8 ± 5, 7 vs -23, 01 ± 3, 6 p value= 0, 032). CONCLUSIONS: Despite normal RV function detected in both TTE and CMR, patients with infero-lateral aMY have lower values of RV longitudinal strain. CMR-FT RV strain analysis has proven to be a useful tool in detecting subclinical RV involvement in patients with aMY.